Taxonomic Study on Blue-green Algal Community on the Forest Floor from Hilly Regions of Darjeeling - Dey, Narottam; Banerjee, Banani; Ghatak, Avijit (Indian Forester, 2010)
Present study represents morpho-taxonomy and diversity of a number of terrestrial Blue-green algae inhabiting on forest floor in hilly regions of Darjeeling. A total of five genera and 11 species were identified and characterized.